TUNJUK AJAR DALAM UMPASA PERKAWINAN ADAT BATAK TOBA - Denny Hartati Purba; Syafrial Syafrial; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research aims to describe the learning contained in the traditional Batak Toba wedding ceremony. This type of research is a qualitative research with descriptive analysis research method which aims to explain clearly the data described about the teaching and learning process contained in the traditional Batak Toba wedding ceremony. The data sources of this research are information obtained directly from the object of research and complementary data from the text of the book Jambar Hata. This research was conducted in Doloksanggul, Humbang Hasundutan Regency, North Sumatra by attending directly the traditional wedding ceremony. The data in this study is the teaching and learning process which is divided into two delivery, namely verbal and non-verbal. Data were analyzed, then classified according to teaching points. Based on the results of the study found 10 teaching points with a total of 19 data. The distribution of the data is (1) verbal teaching shows 15 data, and (2) non-verbal teaching shows 4 data.Keywords: Advice,Wedding rhyme, Batak Toba